The behavior of Brazilian companies shares return under social responsibility - Cavenaghi, Fernanda Bojikian; Pimenta Junior, Tabajara; Antônio, Rafael Moreira; Lima, Fabiano Guasti; Corrêa, Ana Carolina Costa (Revista de Negócios, 2019)
Several scientific studies seek to establish a relationship between the adoption of corporate social responsibility practices and financial and/or economic performance of companies. There are no definitive answers to this question. Compared performance of ISE – Índice de Sustentabilidade Empresarial (Index of Corporate Sustainability) and Ibovespa index, both from Brazilian stock market, is often used to characterize the influence of good business practices in this area. This work investigated this question in an innovative prism. Instead of using directly that index returns series, we constructed a portfolio composed only of companies that remained in ISE portfolio over the five years from 2012 to 2016, and compared their performance with a portfolio of an equal number of companies, taken among the most liquid ones that continuously participated in the Ibovespa portfolio in same period. For this purpose, we used Mann-Whitney averages comparison test, return series stationarity tests – Augumented Dickey-Fuller and Phillips-Perron - and Engle-Granger cointegration test. The results showed higher average returns for portfolio of socially responsible companies, indicating a growth of their returns compared to portfolio of conventional companies, and showed, however, a tendency to balance in long term run.